2021
DOI: 10.1002/smtd.202100901
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐Engineered Homostructure for Enhancing Proton Transport

Abstract: Ultra‐wide bandgap semiconductor samarium oxide attracts great interest because of its high stability and electronic properties. However, the ionic transport properties of Sm2O3 have rarely been studied. In this work, Ni doping is proposed to be used for electronic structure engineering of Sm2O3. The formation of Ni‐doping defects lowers the Fermi level to induce a local electric field, which greatly enhances the proton transport at the surface. Furthermore, ascribed to surface modification, the high concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 42 publications
(22 reference statements)
0
46
0
Order By: Relevance
“…And the O 1s XPS spectra in Li 2.5 Sr 0.75 Zr 1.25 (PO 4 ) 3 could be fitted into three peaks at 532.94, 531.61, and 530.82 eV, which are assigned to the lattice oxygen atoms, oxygen atoms neighboring defects and oxygen atoms of the surface. 35,41,42 The ratio O v /O L for Li 2.5 Sr 0.75 Zr 1.25 (PO 4 ) 3 was significantly higher than SrZr 4 (PO 4 ) 6 , indicating that there are more oxygen vacancies. The increased amount of deficient oxygen species is ascribed to the doping of Sr 2+ in the sites of Zr 4+ .…”
Section: Structural and Morphological Analysismentioning
confidence: 96%
“…And the O 1s XPS spectra in Li 2.5 Sr 0.75 Zr 1.25 (PO 4 ) 3 could be fitted into three peaks at 532.94, 531.61, and 530.82 eV, which are assigned to the lattice oxygen atoms, oxygen atoms neighboring defects and oxygen atoms of the surface. 35,41,42 The ratio O v /O L for Li 2.5 Sr 0.75 Zr 1.25 (PO 4 ) 3 was significantly higher than SrZr 4 (PO 4 ) 6 , indicating that there are more oxygen vacancies. The increased amount of deficient oxygen species is ascribed to the doping of Sr 2+ in the sites of Zr 4+ .…”
Section: Structural and Morphological Analysismentioning
confidence: 96%
“…However, the conventional yttrium-stabilized zirconia (YSZ) electrolyte cannot achieve sufficient ionic conductivity of 0.1 S cm –1 until ∼1000 °C, so the SOFC must be operated at high temperatures to achieve the desired performance, leading to several chemical-thermo-mechanical limitations that delay commercialization. The single-layer (component) fuel cell (SLFC) or the electrolyte layer free fuel cell is gaining attention in recent research developments because it removes the limitations imposed by the electrolyte, resulting in far fewer material selection constraints than conventional three-layer anode/electrolyte/cathode fuel cells. It is also reported that the p–n heterojunctions or Schottky junctions play an extremely important role in overcoming the short circuit problem and improving power output. …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, novel symmetrical CFCs using lithium compounds, that is, Ni 0.8 Co 0.15 Al 0.05 LiO 2 (NCAL) as electrodes with a cell configuration of NCAL/electrolyte/NCAL were reported for low temperatures. These fuel cells have intriguing potential toward commercialization because of good performance and high ionic conductivity below 600 °C. Some researchers reported that the high ionic conductivity is attributed to the surface/interface ionic transportation. For example, Xing et al reported that high concentrations of oxygen vacancies in the CeO 2 surface layer promote the proton transportation . Super proton conductivity of 0.16 S cm –1 was achieved in the as-prepared CeO 2 electrolyte at 520 °C, which is much higher than the bulk oxygen ionic conductivity in doped cerium oxide. , However, the electrolyte is porous in these cells because they are fabricated with the dry press method and have not been sintered at high temperatures.…”
Section: Introductionmentioning
confidence: 99%